Statistical Evaluation of Cost-effectiveness Iinvesting in Staff Development (by the Example of JSC «Volyn-AUTO») (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In this article method for evaluation of cost-effectiveness investing in staff development was improved. We analyzed the qualitative and quantitative indexes movement of the staff at JSC «Volyn Auto». The structure and dynamics of the cost of maintenance and development were examined during five years. We conducted regression analysis that revealed a strong link between staff costs and gross profits of enterprise. Developed linear regression model allowed evaluating the level of economic cost-effectiveness investing in staff development, that affect the growth rate of productivity and profitability
Keywords: linear regression model, statistical evaluation, staff, staff costs, cost-effectiveness